Contrasting effects of plant diversity across arthropod trophic groups in plantain-based agroecosystems - (:unkn) unknown (My University, 2016)
Previous biodiversity studies have shown that plant diversity increases the complexity of arthropod food webs. However, only a few studies have addressed this issue in tropical ecosystems, in which the small annual variations allow the community to approach a steady state. With the goal of optimizing pest management, we studied the effect of plant diversity on the arthropod community in 20 plantain-based fields in Cameroon. Plantain-based agroecosystems are especially useful for studying the effects of plant diversity because they contain few to many non-plantain crop plants and are treated with few or no pesticides or fertilizers. We measured the diversity of cropped plants and the abundance of ground-dwelling arthropods. Five trophic groups of arthropods were identified based on stable isotopic signatures (?13C and ?15N). At the field scale, predator abundance was positively correlated with plant diversity while herbivore abundance displayed the opposite pattern. These strong and inverse effects of plant diversity on predator and herbivore abundances suggest that top-down forces and resource concentration structure the arthropod community in plantain fields. Our findings are consistent with other studies that showed a reduction of interaction and interference between predators in more structured habitats. These findings will help in the design of plantain agroecosystems that enhance pest control.
Keywords: African Research